Subarachnoid haemorrhage of unknown cause: a long term follow-up. Issue 2 (February 1989) - Hawkins, T D; Sims, C; Hanka, R
Abstract : Three hundred and sixteen patients who suffered a subarachnoid haemorrhage of unknown cause were followed up by questionnaire after 2 to 23 years, the average interval being 10 years. Two hundred and fifty one (79.5%) are known to be alive, 49 (15.5%) had died, and 16 (5%) patients were untraceable. The cumulative survival for the whole group after 22 years was 69%, the expected survival being 89%. The certified cause of death of 30 patients was from diseases of the circulatory system, mainly myocardial infarction and cerebrovascular disease, the expected number being 21.8. The results of this survey show a reduced life expectancy for both males and females and suggest that a more guarded view should be taken than is presently the case about the long term prognosis of these patients.